Cultural variation of Macrophomina phaseolina isolates collected from Vigna mungo - R.H. SINGH**, T. PRAMEELA DEVI* and (Indian Phytopathology, 2002)
M. phaseolina was isolated from seeds of urdbean (Vigna mungo) obtained from Coimbatore and Tirunelveli (Tamil Nadu), Guntur and Machilipatnam (Andrah Pradesh), Kottayam (Kerala), Jaipur (Rajasthan), Parbani (Maharashtra), Ranchi (Bihar), Shillong (Maghalaya), Pantnagar (Uttar Pradesh) and New Delhi, India. Isolations were also made from the diseased urdbean plants (stems, roots and pods) collected from Coimbatore, Guntur, Jaipur and New Delhi. In all, 36 isolations were made and the cultures were purified by single hyphal tip culture method. These isolates were grouped into 3 types on the basis of their morphological characters.